2003
DOI: 10.1097/01.tp.0000044360.20396.ab
|View full text |Cite
|
Sign up to set email alerts
|

A short course of cyclosporine immunosuppression inhibits rejection but not tolerance of rat liver allografts1

Abstract: CsA did not significantly inhibit liver transplant acceptance and allowed some activation of T cells and CD25 expression but almost completely inhibited IL-2 and IL-4, which are required for survival of activated T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Circulating and intra-graft levels of pro-inflammatory cytokines, such as IL-6, IL-1β, and TNF-α, are elevated after experimental organ transplantation as well as in clinical studies (Ichikawa et al, 2000). In fact, treatment with immunosuppressive drugs has been shown to prolong allograft survival via the inhibition of pro-inflammatory cytokine expression and production (Murase et al, 1990;Huang et al, 2003). We here found that the expressional levels of these cytokine genes were elevated in transplanted hearts, in which levels were reduced by treatment with db-cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating and intra-graft levels of pro-inflammatory cytokines, such as IL-6, IL-1β, and TNF-α, are elevated after experimental organ transplantation as well as in clinical studies (Ichikawa et al, 2000). In fact, treatment with immunosuppressive drugs has been shown to prolong allograft survival via the inhibition of pro-inflammatory cytokine expression and production (Murase et al, 1990;Huang et al, 2003). We here found that the expressional levels of these cytokine genes were elevated in transplanted hearts, in which levels were reduced by treatment with db-cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of Taqman primers and probes for rat IL-2, IL-4, IL-10, interferon (IFN)-␥, and glyceraldehyde phosphate dehydrogenase have been reported in previous studies (27,28). Quantification of each cytokine mRNA level was calculated using Sequence Detector version 1.7 software (Applied Biosystems) and a standard curve generated by serial dilutions of a sample with high-level cytokine expression, as previously described (8).…”
Section: Quantification Of Cytokine Mrna Expressionmentioning
confidence: 99%
“…MOPC-21 (Sigma, St. Louis, MO) was used as the negative control antibody. The extent of lobular infiltration by cells staining for R73, CD25, and OX39 was calculated as positive cells per millimeter squared as previously described (8). Deposition of IgG1 and IgM antibodies was scored by a semiquantitative system ranging from 0 (undetectable) to 7 (deposition on 100% of section) (8).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 2 more Smart Citations